Role Conflict as Mediator of the Relationship Between Total Quality Management Practices and Role Ambiguity - Teh, Pei Lee (2010)
This study examines the multidimensional and mediating relationships between six TQM practices and role conflict as well as role ambiguity. The six TQM practices are namely, leadership, strategic planning, customer focus, human resource focus, proses management and information analysis. The research model of this study is built from an extensive review of the literature, in particular, TQM and role stressors literature.